Spatial Deflection of Parallel Hydraulic Fractures and Induced Shear Stress Disturbance Under Different Perforation Cluster Spacing Considering Thermal Effects - Wang, Yongliang; Liu, Nana; Cui, Yishuo; Liu, Xuguang (Frontiers in Built Environment, 2022)
Quantitative characterization of fracture network length and morphology in hydrofracturing is crucial for controlling and optimizing fracturing effects. To study the disturbance deflection behaviours of multiple hydraulic fractures, three-dimensional engineering-scale numerical model for multistage fracturing is established to study the shear stress disturbance and unstable propagation behavior of hydraulic fractures under different perforation cluster spacing. In the model, the thermal diffusion, fluid flow and deformation of rock between the rock matrix and fluid in pores and fractures are considered to describe the thermal-hydro-mechanical coupling. In the numerical case study, the derived results show that the thermal effect between fracturing fluid and rock matrix is an important factor affecting fracture propagation, and thermal effects may increase the fracture propagation degree. The size of stress shadow areas and the deflection of hydraulic fractures will increase with the decrease of multiple perforation cluster spacing in horizontal wells. The shear stress disturbance caused by fracture propagation is superimposed in multiple fractures, resulting in stress shadow effect and deflection of fractures.